2020
DOI: 10.4081/ni.2020.8401
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease prevalence, age distribution and staging in Colombia

Abstract: Parkinson’s disease (PD) has the second highest prevalence among neurodege - nerative diseases. In Colombia, PD population dynamics are currently unknown. Health records offer a unique resource to study frequency and multi-morbidity of chronic diseases. The aim of this research is to estimate prevalence and staging using administrative data (AD) provided by Health Maintenance Organizations (HMOs). A cross-sectional study was conducted using 2015 AD from two Colombian HMOs (4.312.928 beneficiaries, 9.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
2
20
1
7
Order By: Relevance
“…PD cases were 53% male and had a mean age of 61.7 years (±12.8 years) and a mean age at onset of 54.1 years (±14.4 years); controls were 33% male and had a mean age of 56.5 years (±14.6 years). Though the sex ratio of PD cases is lower in LARGE‐PD than that of U.S.‐based Hispanic/Latinos, 10 it appears to be concordant with that of other studies in the region 43,44 . Hispanic/Latino populations tend to have a three‐way admixture pattern with contributions from African, European, and Native American ancestry.…”
Section: Resultssupporting
confidence: 82%
“…PD cases were 53% male and had a mean age of 61.7 years (±12.8 years) and a mean age at onset of 54.1 years (±14.4 years); controls were 33% male and had a mean age of 56.5 years (±14.6 years). Though the sex ratio of PD cases is lower in LARGE‐PD than that of U.S.‐based Hispanic/Latinos, 10 it appears to be concordant with that of other studies in the region 43,44 . Hispanic/Latino populations tend to have a three‐way admixture pattern with contributions from African, European, and Native American ancestry.…”
Section: Resultssupporting
confidence: 82%
“…A systematic review showed that the prevalence of dementia in patients with PD (PDD) ranges from 17.4 to 31.5%, with an average of 24.5%, which is higher than that in our cohort. The prevalence of dementia in our Colombian cohort is 4.9% for all patients and 6.9% for patients aged 65 years and older, which is considerably higher than the prevalence of 5.14% observed in the general Chinese population aged 65 years and older [4,10].…”
Section: Epidemiologycontrasting
confidence: 70%
“…Epidemiological data on PD are highly variable across countries. These differences can be explained by the variability in the diagnostic criteria, changes in population age distribution and the access to health care services, including the opportunity to consult with trained doctors and specialists [3][4][5].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson's disease (PD) is a progressive neurodegenerative disorder associated with motional and cognitive function. It is the second-highest prevalent neurodegenerative disease after Alzheimer's disease [195]. As the count of countries affected by an aging society has been growing, the number of people diagnosed with PD is also growing.…”
Section: Parkinson's Diseasementioning
confidence: 99%